PENGARUH PENERAPAN SISTEM PENGENDALIAN INTERN, SISTEM INFORMASI MANAJEMEN DAN PENERAPAN STANDAR AKUNTANSI TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH - Asnida, Nila; Irwansyah, Irwansyah; Aprila, Nila (JURNAL FAIRNESS, 2018)
This study aims to examine empirically the Influence of Government Internal Control Systems (GICS), Regional Management Information Systems (RMIS), and Application of Government Accounting Standards (GAS) to the Quality of Financial Statements (QFS). This research was carried out at the regional government of Bengkulu Province, using a sample of 84 respondents. Data collection methods use surveys, while data analysis techniques used are validity and reliability testing, hypothesis testing is done using linear regression analysis.The results of the study show (1) the application of GICS has a positive effect on the QFS. By continuously strengthening GICS, it will have an impact on improving the QFS. (2) The application of RMIS has a positive effect on the QFS. This shows that the better the implementation of the regional management information system, the more qualified local government financial reports will be. (3) GAS implementation has a positive effect on the QFS. This proves that the better the level of implementation of QFS that is carried out in the preparation of financial statements, it will have a positive impact on improving the QFS.